Study on Sleep Procrastination Behavior and Psychological Prevention Strategies Among University Students During Vocational Awareness Internships - Jiang, XiaoYan; Xie, Li; Wang, ShaoQing (Pacific International Journal, 2024)
The concept of sleep procrastination is a newly introduced notion in the field of health behavior procrastination. It can be summarized as the behavior where individuals, without any external hindrances, still choose to delay their predetermined sleep time. With the rapid development of the socio-economic environment and the internet, people are increasingly going to bed later, making sleep procrastination more prevalent. However, psychological research on sleep procrastination in China remains significantly lacking. This study aims to investigate the current state of sleep procrastination behavior among college students during vocational awareness internships and propose psychological intervention strategies. Through an electronic questionnaire survey of 641 students majoring in Infant Care Services and Management from a vocational college in Weifang, Shandong Province, 541 valid responses were obtained after excluding invalid questionnaires. The results showed that the sleep procrastination behavior of the students was at a moderate to low level, with no significant impact from variables such as only-child status, gender, and place of origin. This study proposes intervention strategies for sleep procrastination behavior among college students through behavior intervention, psychological adjustment, and environmental optimization to improve sleep quality, overall quality of life, and academic performance in vocational awareness .